2019
DOI: 10.21037/jgo.2018.11.07
|View full text |Cite
|
Sign up to set email alerts
|

Does a stoma reduce the risk of anastomotic leak and need for re-operation following low anterior resection for rectal cancer: systematic review and meta-analysis of randomized controlled trials

Abstract: Background: There is a relatively high risk of anastomotic leak in low anterior resection (LAR), associated with significant morbidity and mortality. This systematic review and meta-analysis aims to compare diverting stoma vs. no stoma for LAR in terms of leak rates, reoperations, mortality rates and complication rates. Methods: We systematically performed electronic searches of databases Ovid Medline, PubMed, CCTR, CDSR, ACP Journal Club and DARE from inception to present. Only randomized controlled trials co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 32 publications
2
59
0
2
Order By: Relevance
“…This procedure would reduce the risk of AL, and in case of occurrence the severity of septic complication related to this leak. This role has been confirmed by several meta-analyses (level 2A) [ 46 - 49 ] of which one (level 1A) published in 2019 [ 50 ] including 8 randomized trials and 892 patients. In this meta-analysis, Phan et al [ 50 ] concluded that the diverting stoma significantly reduced the rate of AL and the rate of reoperation after anterior resection for low rectal cancer.…”
Section: Resultsmentioning
confidence: 80%
“…This procedure would reduce the risk of AL, and in case of occurrence the severity of septic complication related to this leak. This role has been confirmed by several meta-analyses (level 2A) [ 46 - 49 ] of which one (level 1A) published in 2019 [ 50 ] including 8 randomized trials and 892 patients. In this meta-analysis, Phan et al [ 50 ] concluded that the diverting stoma significantly reduced the rate of AL and the rate of reoperation after anterior resection for low rectal cancer.…”
Section: Resultsmentioning
confidence: 80%
“…Despite the current recomsmendation for primary anastomosis after a resection procedure, such treatment is associated with a significant risk of anastomotic leak (up to 20% = [ 4 , 5 ]). One way to reduce the risk of leak is to use a diverting ileostomy [ 6 , 7 ]. Although this is currently considered a standard treatment, especially in the group of patients undergoing neoadjuvant radiotherapy or chemoradiotherapy, the technique still has its drawbacks, such as the necessity to perform an additional surgical operation for ileostomy closure, which has a high risk of wound healing complications, particularly surgical site infections (SSI) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some surgeons preferred to perform a routine de-functioning stoma to avoid the confusing situation of leakage and mortality. However, a de-functioning stoma may increase the incidence of either total or stoma-related complications [43,44]. In addition, the presence of a de-functioning stoma demanded additional subsequent surgery for stoma closure, and thus may lead to additional complications [45][46][47].…”
Section: Discussionmentioning
confidence: 99%